PERAN ORANG TUA DALAM PENGELOLAAN SOSIAL EMOSIONAL ANAK USIA DINI SELAMA PEMBELAJARAN DARING - R, Rahmi; Fatimah, Sitti (Institut Agama Islam Negeri Bone, 2024)
The research was conducted to determine the contribution of parents in Asri Kindergarten Waru, Bulu Tempe Village, West Tanete Riattang District, Bone Regency. And to know the social emotional management of early childhood during online learning at Asri Waru Kindergarten, Bulu Tempe Village, Tanete District Riattang Barat, Bone Regency. This research method uses a type of qualitative research, for obtain the desired data researchers using primary data and secondary. Furthermore, it was analyzed by reducing data, presenting data and conclusion. The results of this study indicate that the contribution of parents in online learning at Asri Waru Kindergarten, Bulu Tempe Village, Tanete District West Riattang Bone Regency, as an educator with priority children's interests and children's needs, the role of parents as controllers with regulate the attitude of children, parents as facilitators by providing facilities and infrastructure for children, while parents act as mentors, parents can provide direction or guidance to children. As for social management emotional early childhood during online learning, namely respect where children can respect others, adjust themselves so that children can be accepted environment, and solidarity with children.